Dispersion Energy Enforced Dimerization of a Cyclic Disilylated Plumbylene - Arp, Henning (American Chemical Society, 2012)
[Image: see text] By reaction of 1,4-dipotassio-1,1,4,4-tetrakis(trimethylsilyl)tetramethyltetrasilane with PbBr(2) in the presence of triethylphosphine a base adduct of a cyclic disilylated plumbylene could be obtained. Phosphine abstraction with B(C(6)F(5))(3) led to formation of a base-free plumbylene dimer, which features an unexpected single donor–acceptor PbPb bond. The results of density functional computations at the M06-2X and B3LYP level of theory indicate that the dominating interactions which hold the plumbylene subunits together and which define its actual molecular structure are attracting van der Waals forces between the two large and polarizable plumbylene subunits.